Analisis Kebijakan Standar Kompetensi Lulusan Pendidikan Guru Sekolah Dasar dalam Kurikulum Nasional - Novia Rahma Safitri; Sriwildani Sriwildani Sriwildani; Regita Berlian Widodo; Rizki Ananda Ananda; Ramdhan Witarsa Witarsa (Universitas Negeri Makassar, 2022)
This study aims to describe the policy of competency standards for elementary school teacher education graduates in the national curriculum. This research method uses qualitative research methods with a literature review approach. The research stages were carried out starting from article collection, article reduction, article display, discussion, and conclusion. Sources of research data are articles from accredited national journals in the last 6 years (2017-2022). The results showed that from 19 articles, 3 articles were obtained that matched the title topic. Elementary school teacher education is integrated in the national curriculum as an educational science that is applied to related subjects that are mandatory for all undergraduate teacher candidates for elementary school teacher education and in its renewal primary school teacher education as the main goal to prepare prospective teachers. elementary school teachers through courses that are relevant to the times. The renewal of courses in primary school teacher education needs to be reviewed. It is necessary to review the policy on competency standards for elementary school teacher education graduates in the national curriculum.